2015
DOI: 10.18549/pharmpract.2015.03.583
|View full text |Cite
|
Sign up to set email alerts
|

Implementing simulated learning modules to improve students’ pharmacy practice skills and professionalism

Abstract: Background:Effective communication enables healthcare professionals and students to practise their disciplines in a professional and competent manner. Simulated-based education (SBE) has been increasingly used to improve students’ communication and practice skills in Health Education.Objective:Simulated learning modules (SLMs) were developed using practice-based scenarios grounded in effective communication competencies. The effect of the SLMs on Pharmacy students’ (i) Practice skills and (ii) Professionalism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 23 publications
0
54
0
1
Order By: Relevance
“…According to Gaba (2004) simulation-based education is an educational approach that uses simulation, in its many applications and modalities, to achieve educational goals through experiential learning. International literature emphasizes the need to utilize an assortment of technology-based learning environments to train and educate health professionals (Cook et al 2011;Keppell et al 2015) and specifically for pharmacists (Fejzic and Barker 2015;Smith and Benedict 2015). Multiple studies support embedding technology-enhanced, simulation-based education into pharmacy curricula, such as online learning that is enriched by pre-recorded role plays with actors or simulated participants, virtual patients, task simulations and/or interactive platforms that simulate a specific skill or competency (Fejzic and Barker 2015;Kirwin et al 2013;Loke et al 2011;Regan et al 2014;Salter et al 2014;Smith and Benedict 2015;Veettil and Rajiah 2016;Vyas et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to Gaba (2004) simulation-based education is an educational approach that uses simulation, in its many applications and modalities, to achieve educational goals through experiential learning. International literature emphasizes the need to utilize an assortment of technology-based learning environments to train and educate health professionals (Cook et al 2011;Keppell et al 2015) and specifically for pharmacists (Fejzic and Barker 2015;Smith and Benedict 2015). Multiple studies support embedding technology-enhanced, simulation-based education into pharmacy curricula, such as online learning that is enriched by pre-recorded role plays with actors or simulated participants, virtual patients, task simulations and/or interactive platforms that simulate a specific skill or competency (Fejzic and Barker 2015;Kirwin et al 2013;Loke et al 2011;Regan et al 2014;Salter et al 2014;Smith and Benedict 2015;Veettil and Rajiah 2016;Vyas et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that individuals with practical experience had higher self-efficacy with regard to implementing the related behavior; moreover, self-efficacy could be improved through simulation scenarios and experiential learning via models and practice. 33 , 34 Similarly, we found that RTs with clinical PR experience or training had higher levels of self-efficacy. To increase self-efficacy, clinical training courses in PR including education courses and clinical practice training should be increased in the future.…”
Section: Discussionmentioning
confidence: 52%
“…FW. This is supported by the study of Fejzic and Barker (2015), who found that pharmacy students' professionalism significantly increased after they engaged in a simulation experience. Through HFS, students have an opportunity to practice and develop these skills through experiential learning.…”
Section: Resultsmentioning
confidence: 74%